Perancangan Customer Relationship Management (CRM) menggunakan Metode SEO berbasis Website (Studi Kasus: CV. Tips Indonesia) - Syaifudin Anshori; Buce Trias Hanggara; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
CV. Tips Indonesia is a human resource development agency. The author found that there were customer management relationship (CRM) activities that were less effective in finding new customers. The indication that this is happening is the ineffective marketing of the online media. Based on the indication of the problems that occur, the researcher will evaluate the Customer Management Relationship (CRM) that is being carried out. Researchers will use the Search Engine Optimization (SEO) method on the website of CV. Tips Indonesia for automating the marketing that is being done in order to expand the market it has and cover more customers. The method of Search Engine Optimization (SEO) is carried out using 2 methods, namely: on-site optimization and off-site optimization. Meanwhile, the analysis of the success of the Search Engine Optimization (SEO) process is carried out using 4 stages of analysis. The first is website analysis on google pages. Secondly, analysis of visitor traffic using google analytics, analysis using the alexa.com website to find out the website rankings globally and conduct a domain quality analysis from the tips-indonesia.com website. On the google website page analysis has increased. Before being optimized the website was outside the top 10 of Google and after 3 months of optimization, the website had increased to page 3 of Google. For website visitor traffic analysis, visitor traffic increases from before optimization activities. At the time before optimization the website had 0 visitors for a month until after optimization for 3 months the website had 642 visitors for a month. And in the global ranking analysis, the website has increased from 9,883,983 to 8,082,005. Ahrefs rank shows the website's ranking from tips-indonesia.com is ranked 8,930,581 globally. Then for UR (URL Rating) and DR (Domain Rating) which shows